Sarah Rosetta Wakeman papers - Wakeman, Sarah Rosetta, 1843-1864.
Photocopies of Wakeman's letters to her family while serving with the 153rd New York Infamtry Regiment as Pvt. Lyons Wakeman. Most of the letters were written from Washington, D.C., and Alexandria, Va., with a few later ones from Louisiana.
Photocopies.
Resident of Afton, N.Y., who assumed a male identity and served in the 153rd New York Infantry Regiment during the Civil War under the name Lyons Wakeman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Published as: An uncommon soldier: the Civil War letters of Sarah Rosetta Wakeman, alias Private Lyons Wakeman, 153rd Regiment, New York State Volunteers/edited by Lauren Cook Burgess; with a foreword by James M. McPherson. Pasadena, Md.: The Minerva Center, 1994.
Keywords: Wakeman family; United States. -- Army. -- New York Infantry Regiment, 153rd (1862-1865); Women soldiers -- United States -- History -- 19th century; Afton (N.Y) -- History; Alexandria (Va.) -- History; Louisiana) -- History -- Civil War, 1861-1865.; New York (State) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Participation, Female; United States -- History -- Civil War, 1861-1865 -- Personal narratives; Virginia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Soldiers